2010
DOI: 10.1524/ract.2010.1769
|View full text |Cite
|
Sign up to set email alerts
|

Influence of iron redox transformations on plutonium sorption to sediments

Abstract: Plutonium / Subsurface transport / Redox / XANES / Iron / KineticsSummary. Plutonium subsurface mobility is primarily controlled by its oxidation state, which in turn is loosely coupled to the oxidation state of iron in the system. Experiments were conducted to examine the effect of sediment iron mineral composition and oxidation state on plutonium sorption and reduction. A pH 6.3 vadose zone sediment containing iron oxides and iron-containing phyllosilicates was treated with various complexants (ammonium oxal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
38
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 28 publications
9
38
0
Order By: Relevance
“…Thus, increasing the Fe(II) content of the system should correlate to an increase in reaction (sorption + reduction) kinetics. This expected trend was confirmed by Hixon et al (2010), who observed a decrease in the rate of Pu(V) reduction to Pu(IV) when the concentration of Fe(II) in SRS sediments was decreased. Therefore, magnetite should exhibit faster kinetics than hematite or goethite.…”
supporting
confidence: 62%
“…Thus, increasing the Fe(II) content of the system should correlate to an increase in reaction (sorption + reduction) kinetics. This expected trend was confirmed by Hixon et al (2010), who observed a decrease in the rate of Pu(V) reduction to Pu(IV) when the concentration of Fe(II) in SRS sediments was decreased. Therefore, magnetite should exhibit faster kinetics than hematite or goethite.…”
supporting
confidence: 62%
“…Previous sorption experiments indicated that changes in the sorption behavior were continuously observed over a 60 day period and were attributed to reduction of Pu(V) to Pu(IV) [34]. Similar surface mediated reduction of Pu(V) has been observed on a variety of pure minerals and soils [35][36][37][38][39][40][41] and sorption of Pu(IV) is considerably stronger than Pu(V). A double layer surface complexation model fit to the data is shown as the solid lines in Figure 8 and the aqueous and surface complexation constants are given in Table 3.…”
Section: Ternary Sorption Experimental and Modeling Studiesmentioning
confidence: 59%
“…At approximately 50 m 2 /L of each mineral and pH 8, the kinetic reaction rate for magnetite (1.97 g/L) was an order of magnitude greater than hematite (1.38 g/L) or goethite (0.30 g/L) [32,33]. Hixon et al [40] studied the influence of iron redox transformations on Pu sorption to SRS sediments that consisted of goethite-coated sands and found that native Fe(II) in the sediments was responsible for the reduction of trace levels of Pu, the rate of Pu(V) reduction to Pu(IV) decreased as the concentration of Fe(II) in SRS sediments was decreased, in agreement with the iron oxide surface-mediated reduction mechanism of Pu(V).…”
Section: Distribution Coefficient and Sorption Percentagementioning
confidence: 96%